ANALISIS PELINDUNGAN HUKUM TERHADAP HAK SIAR DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2002 TENTANG PENYIARAN DAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA (CONTOH KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 629/PDT.SUS-HKI/2019) - Sarah Mawaddah Shabariyah; Christine S.T. Kansil (Fakultas Hukum Universitas Tarumanagara, 2020)
There were so many violations of the 2014 Brazil World Cup soccer match broadcast. The 2014 Brazil World Cup broadcast violations were resolved through litigation, namely the Commercial Court because it was a violation of the Related Rights. There are two laws and regulations in positive law in Indonesia related to broadcast rights.The Broadcasting Law and UUHC are the legal umbrella for protecting the implementation of broadcast rights.The realization of these two laws regulates two different things. The Broadcasting Law regulates the license of a broadcasting institution while the UUHC regulates the protection of broadcast work content which is included in Related Rights, thus raising questions regarding how to protect broadcast work holders and control broadcast rights in Indonesia. The method used is juridical empirical. The results of the research show that protection for broadcast work holders who can also be called creators is protected by Article 40 UUHC which is basically included in protected works, thus UUHC has provided protection for broadcast works and broadcast work holders even though Article 40 UUHC does not explicitly mention about broadcast works themselves, but broadcast works are protected by broadcasting institutions based on Article 3 letter b of the UUHC, namely Related Rights and the supervision of Broadcast Rights in Indonesia is currently being monitored by KPI based on the mandate of the Broadcasting Law. In practice,not only KPI can supervise, but the public can participate if there is a broadcast without permission or license from the holder of the broadcast work.